Alex the parrot : no ordinary bird - Spinner, Stephanie (Alfred A. Knopf, 2012)
Recounts the true story of an African grey parrot who was the subject of a graduate student's scientific experiment on animal intelligence and who astonished everyone with its ability to add, understand concepts and speak hundreds of words.